Measurement of indirect CP asymmetries in D0 → K-K+ and D0 → π-π+ decays using semileptonic B decays - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
Time-dependent CP asymmetries in the decay rates of the singly Cabibbo-suppressed decays D0 → K−K+ and D0 → π−π+are measured in pp collision data corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment. The D0 mesons are produced in semileptonic b-hadron decays, where the charge of the accompanying muon is used to determine the initial state as D0 or D0. The asymmetries in effective lifetimes between D0 and D0 decays, which are sensitive to indirect CP violation, are determined to be AΓ(K−K+) = (−0.035 ± 0.062 ± 0.012)%, and AΓ(π−π+) = (0.033 ± 0.106 ± 0.014)% where the first uncertainties are statistical and the second systematic. This result is in agreement with previous measurements and with the hypothesis of no indirect CP violation in D0 decays.